155k views
0 votes
Solve the equation above

Solve the equation above-example-1
User Asdasdad
by
5.7k points

1 Answer

0 votes

Answer:

X = -2

Explanation:

1/2 X (5X-8) = -9

multiply both sides of the equation by 2

2 X 1/2 X (5X - 8) = 2 X (-9)

1 X (5X - 8) = 2 X (-9)

Reduce the numbers with the greatest common divisor 2

5 x -8 = 2 x (-9)

5 x -8 = -18

Move constant to the right by adding its opposite to both sides

5X -8 + 8=-18 + 8

Then eliminate the opposites

5X = -18 + 8

Calculate the sum

5X = -10

Divide both sides of the equation by 5

5X DIVIDE 5 = -10 DIVIDE BY 5

X = -10 DIVIDE BY 5

X = -2

User Leon Li
by
5.8k points